Second Five Year Plan West Godavari District Review of Progress 1956-61 - Planning Commission (Planning Commission, 1956)
During the Second Plan period an amount of Rs. 478.361 lakhs was spent on various Development Programmes in West Godavari District. The following table shows the distribution of expenditure among the various Major Heads of Development.
West Godavari District